Maternal smoking during pregnancy negatively affects brain volumes proportional to intracranial volume in adolescents born very preterm - Ekblad, Mikael O.; Ngum, Peter; Merisaari, Harri; Saunavaara, Virva; Parkkola, Riitta; Setänen, Sirkku (Frontiers in Human Neuroscience, 2023)
Background: Maternal smoking during pregnancy has been shown to associate with smaller frontal lobe and cerebellar volumes in brain magnetic resonance imaging (MRI) at term age in very preterm infants. The aim of this study was to examine the effect of maternal smoking during pregnancy on volumetric brain MRI findings at 13 years. We hypothesized that adverse effects of smoking during pregnancy on brain volumes are still seen during adolescence. Methods: Included adolescents were born very preterm (gestational age <32 weeks and/or birth weight ≤1500 grams) between April 2004 and December 2006 at the Turku University Hospital, Finland. Information on maternal smoking status (yes or no) during pregnancy was collected from medical records and maternal questionnaires before discharge. Adolescents underwent volumetric brain MRI at 13 years of age. Image postprocessing was performed with Freesurfer. Regional volumes, cortical thickness, surface area, and curvature were computed from 33 cortical regions of interest. Additionally, volumes were calculated for 18 subcortical regions, as well as for white matter, gray matter, and intracranial volume. We normalized quantified absolute volumes for head size by dividing volumes with corresponding intracranial volumes. False Discovery Rate (FDR) correction for multiple comparisons across regions was used. Results: 9/44 (21%) adolescents had been exposed to maternal smoking during pregnancy. No statistically significant differences in absolute volumes were observed between the groups (p>0.05). Regarding volumes proportional to intracranial volume, the adolescents in the exposed group exhibited smaller gray matter volumes in the inferotemporal (FDR corrected p= 0.022) and parahippocampal (p=0.018) regions compared to the unexposed group. The surface area in the exposed group was also smaller in the parahippocampal (p=0.046) and postcentral (p=0.046) regions compared to the unexposed group. No statistically significant differences after correction for multiple comparisons were found for either curvature or cortical thickness between the groups. Conclusion: Maternal smoking exposure during pregnancy may have long-term effects on brain volumes up to 13 years in adolescents born very preterm. Our findings emphasize the importance of smoking-free pregnancy.